(untitled) (The Review of Diabetic Studies, 2025)
Palliative care aims to improve the quality of life of patients with life-threatening diseases by preventing suffering and providing relief from pain and associated discomfort. However, palliative care in diabetes has not received much attention and its integration into standard diabetes management is rarely practiced. It is important to identify and manage the risks that affect mortality in diabetes as early as possible. Early initiation of palliative care in diabetes may have a positive impact on managing diabetic complications. Advanced care planning (ACP) is important for patients to make well-thought-out decisions for future healthcare. Besides, tools such as Gold Standards Framework (GSF) can be used for prognostication. During the management of diabetes, glycemic targets, management of diabetic medication, management of diabetes complications and diabetes education are important aspects. The use of diabetogenic medications, such as corticosteroids, in diabetic patients for treating other conditions requires clinicians to carefully consider the risks and benefits. Moreover, complementary and alternative medicine (CAM) in diabetes palliative care is an attractive option depending on the patients’ preferences. Existing diabetes management guidelines and protocols are very helpful with the treatment plan, but they are unlikely to consider patients’ needs and preferences. Therefore, palliative care should not be reserved for only severe patients, and there is a need for new guidelines to integrate palliative care into regular diabetes care.